Synthesis of boron nitride nanotubes and their applications - Saban Kalay (Beilstein Journal of Nanotechnology, 2015)
Boron nitride nanotubes (BNNTs) have been increasingly investigated for use in a wide range of applications due to their unique physicochemical properties including high hydrophobicity, heat and electrical insulation, resistance to oxidation, and hydrogen storage capacity. They are also valued for their possible medical and biomedical applications including drug delivery, use in biomaterials, and neutron capture therapy. In this review, BNNT synthesis methods and the surface modification strategies are first discussed, and then their toxicity and application studies are summarized. Finally, a perspective for the future use of these novel materials is discussed.